Can Programming Be Liberated, Period? - Harel, David (Computer (00189162), 2008)
The article discusses computer programming. Programming involves the tedious tasks of writing out a program as a symbolic, textual, or graphical artifact, specifying requirements separately from the program, and having to structure the program's behavior in line with the system's structure. Programmers are hoping to change the tedium involved in programming with "play-in," which is a guiding process that is interactive and doesn't need the programmer to sit and prepare an artifact. Play-in also includes specifying requirements and doesn't require a programmer to separately specify behaviors as it will all be included in the "play-in" process.